1359. Activity of Meropenem/Nacubactam Combination Against Gram-Negative Clinical Isolates: ROSCO Global Surveillance 2017. (26th November 2018) - Okujava, Rusudan; Garcia-Alcalde, Fernando; Haldimann, Andreas; Zampaloni, Claudia; Morrissey, Ian; Magnet, Sophie; Kothari, Nimmi; Harding, Ian; Bradley, Kenneth
Abstract: Background: Nacubactam (NAC, OP0595, RG6080) is a novel member of the diazabicyclooctane inhibitor family with a dual mode of action, acting as a β-lactamase inhibitor and an antibacterial agent by means of PBP2 inactivation. NAC restores and extends the activity of β-lactam antibiotics, such as meropenem (MEM), when used in combination against a variety of carbapenem-resistant Enterobacteriaceae (CRE). The first year results of the ROSCO surveillance study for MEM/NAC against contemporary clinical isolates are presented here. Methods: Isolates ( n = 4, 695) collected in 2017 from 50 sites in the United States and European hospitals included 30 different species of Enterobacteriaceae (EB, n = 3, 306), Pseudomonas spp. ( n = 960) and Acinetobacter spp. ( n = 429). The predominant species of EB are shown in figure below. MICs were determined by broth microdilution following CLSI methodology for MEM/NAC at a fixed 1:1 ratio (w:w) and by titrating MEM with a constant concentration of NAC at 4 mg/L. Results were compared with MIC values of MEM and NAC alone and standard of care antibiotics, including ceftazidime/avibactam (CAZ/AVI). Results: MIC50/90 for MEM, NAC, and MEM/NAC against all EB isolates and by species are shown in the figure below. NAC alone displayed a bimodal MIC distribution for EB, with a prominent separation at ≤4 mg/L. MEM/NAC 1:1 inhibited 99.5, 99.7, and 99.9% of the 3, 306 EB isolates tested, at ≤2, ≤4, and ≤8 mg/L, respectively; while MEM inhibited 96.5, 96.8, and 97.3% of the isolates at the same concentrations. Of 117 (3.5% of total EB) MEM nonsusceptible (by EUCAST) and multidrug resistant (MDR, by Magiorakos AP, et al., 2012) EB, 87.2, 92.3, and 96.6% were inhibited by MEM/NAC 1:1 at ≤2, ≤4, and ≤8 mg/L, respectively. Additionally, MEM/NAC1:1 displayed MIC ≤8 mg/L for 33 out of 37 CAZ/AVI-resistant MDR EB isolates. MEM/NAC had a similar activity to MEM alone against Pseudomonas spp. and Acinetobacter spp. Conclusion: MEM/NAC combination shows excellent in vitro activity against current clinical EB isolates and the potential to extend MEM activity to MDR, MEM nonsusceptible and CAZ/AVI-resistant isolates, which supports the continued clinical development of MEM/NAC for infections caused by CREs. This project has been funded in part under HHS BARDA Contract HHSO100201600038C. Disclosures: R. Okujava, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Employee, Salary. F. Garcia-Alcalde, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Employee, Salary. A. Haldimann, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Employee, Salary. C. Zampaloni, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Employee, Salary. I. Morrissey, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Research Contractor, Contracting fee to IHMA. S. Magnet, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Research Contractor, Contracting fee to IHMA. N. Kothari, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Research Contractor, Contracting fee to IHMA. I. Harding, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Research Contractor, Contracting fee to Micron. K. Bradley, Roche Innovation Center Basel, F. Hoffmann-La Roche Ltd., Basel, Switzerland: Employee, Salary.